Distortion of digital panoramic radiographs used for implant site assessment - Rayyan Abdulhamid Kayal (Wolters Kluwer Medknow Publications, 2016)
Aims: This study is conducted to determine the amount of distortion of digital panoramic radiographs. Materials and Methods: Panoramic radiographs of all patients who received dental implants in the years 2012 and 2013 were selected from the records at the faculty of dentistry, King Abdulaziz University. Radiographs were analyzed using the R4 Kodak Software for linear measurements of implants length and width. The measurements were compared to the actual size of the implant, and the amount of distortion was calculated. Results: A total of 169 implants were analyzed. Horizontally, there was a statistically significant increase of 0.4 mm in width in the radiographic measurement compared to the actual size in the incisor region. Vertically, the sample overall exhibited a decrease by 0.4 mm compared to the actual size. Incisors had the highest difference with a decrease of 1.7 mm in the radiographic measurements compared to actual size. The highest distortion was found in the incisor region for both diameter and length (1.1 and 0.86), respectively. Conclusion: Digital panoramic radiographs show minimal to no distortion. The highest distortion is found in the anterior area.